Toward sustainable development of a landfill: landfill to landscape or landscape along with landfill? a review - Nochian, Ashkan; Mohd Tahir, Osman; Maulan, Suhardi; Ding, Rui (Universiti Putra Malaysia Press, 2019)
Among prevalent methods of disposal for municipal solid waste, landfilling is the most common one. A landfill requires a piece of land and receive a huge amount of wastes for a certain period of time. Many landfills all around the world are located into or nearby urban areas where the land is scarce and highly demanded. Therefore, an important question arises on how to re-use this piece of threatening land. The aim of this study is to highlight the benefits of landscape work with the roles of landscape architects or equivalent disciplines to succeed a sustainable development of a landfill site not only after the landfill being closed but also from the beginning of it. To achieve this, a comprehensive investigation has been done among related literature to address these issues and prove that landscape work is one of the key factors that can lead a landfill project to a more successful and beneficial one which eventually makes the project sustainable. The findings of the study are useful for those who are engaging in landfill industries both practitioners and academicians and will contribute knowledge about sustainable development of landfill from a different perspective.